Ardisia pyrotechnica (Primulaceae-Myrsinoideae), a new species from Borneo - Julius, Avelinah; Tagane, Shuichiro; Kajita, Tadashi; Jelani, Nur Safinas; Mohamad, Mohizah; Utteridge, Timothy M.a. (Phytotaxa, 2021)
Ardisia pyrotechnica Julius, Tagane & Utteridge (Primulaceae-Myrsinoideae) is described and illustrated as a new species from Sarawak, Borneo. The new species is assigned into Ardisia subgenus Pyrgus based on its inflorescence terminal on specialized lateral branches below the indeterminate primary axis, which is arising directly from the stem. Remarkable for the massive inflorescences subtended by two large elliptic foliose bracts and the large pinkish-white sepals; a preliminary conservation status, photographs and a line illustration are also provided.